PREVENTING EARLY CHILDHOOD CARIES:Preventive behavior of mothers in Banjar district, Indonesia - -, Rahimayant; Keiwkarnka, Boonyong; Sillabutra, Jutatip (Journal of Public Health and Development, 2012)
Early Childhood Caries (ECC) is a serious problem worldwide, and particularly in developing countries such as Indonesia. Mothers are often the major influence on their children’s health, which makes them key players in the prevention of disease, including ECC. This paper describes a cross-sectional descriptive study which investi- gated the factors related to the preventive behavior of mothers regarding ECC, such as their socio-demographic characteristics, knowledge and perception regarding dental caries, and sources of information and social support. Face-to-face interviews with 300 mothers in Banjar district, Indonesia, whose preschool children were regis- tered in kindergartens or playgrounds during data collection, were conducted to assess how they sought to prevent dental caries in their young children. Informed consents were signed by them prior to the interviews. Data were then analyzed using descriptive statistics and chi-square tests to explore associations between factors commonly associated with ECC and the mothers’ preventive behavior. Study results reveal that more than half of the mothers had poor preventive behavior; nearly two thirds were between 25 and 35 years old; almost half had finished high school; and about two thirds were housewives with average monthly family incomes of 2,759,933 rupiahs (9570.49 Baht). Maternal age, education and occupation were factors which were found to have significant association with mothers’ dietary habits for their children. Social support was also found to have a significant association with the regular dental check up aspect. Nowadays, many wives have to join the workforce, not only for economical reason but also for women’s self- achievement. It makes them less able to devote their time to child-rearing. To fill the gap, the role of the preschools and daycare centers is becoming more important. Therefore, the quality of these institutions should be raised to meet the responsibility of achieving better dental health for young children.